The Effect of Members' Interest in Credit and the Risk of Bad Debts on the Determination of Credit Limits at the Koperasi PPA Sejahtera Site BIB - Ulandari, Suci; Muliyani (PT Katersi Minar Permata, 2025)
This study aims to analyze the effect of member credit interest and bad credit risk on credit ceiling setting at the Koperasi PPA Sejahtera Site BIB . Credit ceiling policy is an important instrument in financing management that serves to control credit risk. The setting of disproportionate ceilings often causes problems such as high credit risk, decreased liquidity, and an imbalance in the cooperative's cash flow. This study uses a quantitative method with data collection techniques through interviews, observation, and documentation of the cooperative's management and members. The data obtained was then analyzed to describe the relationship between the application of credit ceilings and indicators of member credit interest and credit default risk. The results of this study indicate that the application of an appropriate credit ceiling policy can increase the credit interest of cooperative members and improve the efficiency of fund distribution and reduce credit default risk.